2021
DOI: 10.1007/s10443-021-09903-0
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Thermoplastic Composite for Marine Applications: Comparison of the Effects of Aging on Mechanical Properties and Diffusion Mechanisms

Abstract: This article investigates and compares the effects of hydrothermal aging on carbon fibre / Elium™ thermoplastic composite and on carbon fibre / vinylester thermoset composite for marine application. Accelerated aging tests are performed by immersion in deionised water at 70 °C.Water diffusion, monitored by regular weighing, shows that both composites as well as Elium™ resin exhibit non-Fickian behaviour. Analytical models are proposed to fit the experimental curves and to identify and compare diffusion paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…The second process was more active when the samples were aged at 60 • C in water leading to voids. Frej et al found fibre/matrix interface weakening and increased void content on CF/Elium® due to leaching phenomena [27]. Similar results were observed in the present case where after one month both weight gain and weight loss due hydrolysis of the binder was observed, however after three month the second phenomena was more prevalent.…”
Section: Environmental Aging and Physical Propertiessupporting
confidence: 90%
See 2 more Smart Citations
“…The second process was more active when the samples were aged at 60 • C in water leading to voids. Frej et al found fibre/matrix interface weakening and increased void content on CF/Elium® due to leaching phenomena [27]. Similar results were observed in the present case where after one month both weight gain and weight loss due hydrolysis of the binder was observed, however after three month the second phenomena was more prevalent.…”
Section: Environmental Aging and Physical Propertiessupporting
confidence: 90%
“…The drastic reduction after three months of immersion can be attributed to the leaching of binder phase and presence of voids in the interply region (Fig. 1c and d) [27]. This results in early damage at the interlaminar region.…”
Section: Mechanical Propertiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Several studies on this subject exist in the literature. 1,[16][17][18] Shao et al (2021), hydrothermally aged glass fiber/polycarbonate and glass fiber/nylon six composite samples in 80°C pure water for 25, 100, 400, 900 and 1600 hours. They investigated the water absorption behavior of the aged samples.…”
Section: Introductionmentioning
confidence: 99%
“…24,31 Recently, a number of studies have been reported in the literature on Elium ® -based composite laminates manufactured using the VARTM technique, and many of these studies focus on the mechanical properties of these novel composites. [31][32][33][34][35][36][37][38][39][40] Several breakthroughs have already been reported in terms of tensile properties, 35 fracture toughness, 42 impact performance, 43 and flexural response, 44 where the fiber-reinforced Elium ® composites have exhibited significantly superior mechanical properties compared to the conventional thermosetting epoxy composites. Similarly, multiple studies have also reported comparable shear strengths in both Elium ® and epoxy composites.…”
Section: Introductionmentioning
confidence: 99%